Adrenal Cushing's syndrome in pregnancy: Clinical and molecular characterisation of a case. (March 2016) - Trinh, Anne; Chan, Irene; Alexiadis, Maria; Pell, Medina; Kumar, Beena; Fuller, Peter J
Background: Cushing's syndrome is rare during pregnancy and more commonly due to adrenal pathology, in contrast to the non-pregnant population. Increased levels of cortisol-binding globulin and placental production of corticotropin-releasing hormone and adrenocorticotropic hormone complicate the diagnostic strategies usually employed. Case: A 32-year-old G1P0 at 15/40 gestation presented with severe peripheral oedema and excessive weight gain. Examination revealed pitting oedema to the abdominal wall, wide violaceous striae, moon facies and acne. Cortisol excess was confirmed with elevated 24 h urinary free cortisol, raised midnight salivary cortisol and lack of diurnal variation. Adrenocorticotropic hormone ranged between 22 and 36 pg/ml (5–8 pmol/L). Fetal ultrasound confirmed a single live intrauterine gestation with an incidental finding of a maternal left adrenal mass. Magnetic resonance imaging confirmed an adrenal mass measuring 3.0 × 4.4 × 4.1 cm. She underwent a laparoscopic left adrenalectomy at 18 weeks' gestation without complication. Her postoperative cortisol level was undetectable. Hydrocortisone replacement was commenced with slow weaning as an outpatient. Histology was consistent with an adrenal adenoma. Immunohistochemistry revealed strong staining for the luteinising hormone/choriogonadotropin receptor, and expression of the luteinising hormone/choriogonadotropin receptor gene was in the range seen in normal ovary. DNA analysis revealed a mutation in GNAS encoding the Gα subunit in the cyclic adenosine monophosphate pathway. Conclusion: Cushing's syndrome may present in pregnancy as a result of βhCG acting on the luteinising hormone/choriogonadotropin receptor over-expression by the adenoma amplifying the aberrant cyclic adenosine monophosphate signaling implicated in the development of cortisol-secreting adenomas.